Antioxidants and Bioactive Compounds in Food: Critical Review of Issues and Prospects - Mia Kurek; Nadjet Benaida-Debbache; Ivona Elez Garofulić; Kata Galić; Sylvie Avallone; Andrée Voilley; Yves Waché (Antioxidants, 2022)
This review paper gives an insight into the effective delivery mechanisms for health-promoting substances and highlights the challenges of using antioxidants and bioactives in foods. The selection criteria for choosing bioactives and their extraction in bioavailable form with their adequate incorporation techniques and delivery mechanisms are covered. Moreover, an overview of existing methods for determination of bioactivity is given. The importance of scientifically evaluating the effects of foods or food components on consumer health before making claims about the healthiness is aligned. Finally, a scientific perspective on how to respond to the booming demand for health-promoting products is given, and we acknowledge that despite the work done, there are still many challenges that need to be overcome.